2015
DOI: 10.1097/ijg.0b013e3182a0761c
|View full text |Cite
|
Sign up to set email alerts
|

Binocular Visual Field Impairment in Glaucoma and At-Fault Motor Vehicle Collisions

Abstract: Purpose To evaluate the association between binocular visual field defects in drivers with glaucoma and risk of motor vehicle collision (MVC) involvement. Methods A retrospective cohort study was conducted on 438 drivers with glaucoma aged ≥ 55 years old using data from 1994 through 2000. Demographic, clinical, and driving characteristics were obtained from chart abstractions and patient survey. Binocular field measures were generated by combining data from the monocular (central 24° radius) fields whereby t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 21 publications
4
26
0
2
Order By: Relevance
“…These results support existing evidence that binocular VF loss impacts driving14 7 23 24 and may indicate that increased motor vehicle accident rates for patients with VF loss are related, at least in part, to an impaired ability to detect hazards in a timely manner. Worsening performance was not related to a slower visual processing time in the Trail B assessment, implying that the effects shown were visual, as opposed to being related to the increased cognitive demands of the task.…”
Section: Discussionsupporting
confidence: 85%
“…These results support existing evidence that binocular VF loss impacts driving14 7 23 24 and may indicate that increased motor vehicle accident rates for patients with VF loss are related, at least in part, to an impaired ability to detect hazards in a timely manner. Worsening performance was not related to a slower visual processing time in the Trail B assessment, implying that the effects shown were visual, as opposed to being related to the increased cognitive demands of the task.…”
Section: Discussionsupporting
confidence: 85%
“…Previous research has found that older age is associated with higher crash risk in those with conditions affecting vision. For example, a recent study by McGwin and colleagues found that drivers with glaucoma over the age of 54 years, who had severely impaired binocular visual fields, had a higher risk for at‐fault motor vehicle crash involvement, compared to those with less severe or no impairment. Similarly, Huisingh and colleagues assessed 2,000 licenced drivers aged 70 and older in central Alabama and found that drivers with visual field impairment have an increased rate of at‐fault motor vehicle crashes compared to those with less impairment or normal visual fields.…”
Section: Discussionmentioning
confidence: 99%
“…[14] Recently Kwon et al reported that the rate of MVCs was 1.65 times higher in drivers with glaucoma (n = 206, 37 subjects (18%) had a history of MVCs) compared with those without glaucoma (n = 1,794, 219 subjects (13%) had a history of MVCs). [8] These results suggest that glaucoma is significantly associated with an increased likelihood of MVC occurrence. However, these studies were conducted in a cross sectional manner so it is possible that persons with glaucoma may simply recall a higher number of MVCs.…”
Section: Introductionmentioning
confidence: 86%